Utveckling av ett webbaserat administrativt system En webbapplikation implementerad med ramverket Symfony - Gunnarsson, Daniel; Nelson, Boel; Panditha, Jennifer; Ljunggren, Sebastian; Stråvik, Isak; Jonsson, Hedvig (My University, 2014)
This report describes the implementation of a web-based administrative system for the non-profit organization Intize. It was constructed using an agile work process along with a close cooperation with Intize. Based on requests from Intize, a requirement specification was formulated which was updated as the requests changed. In parallel with the formulation of the requirement specification, functionality was implemented in order of assigned priority. User testing was conducted continuously throughout the project to test new or modified functionality. The result was an administrative web application for Intize, implemented in PHP using the framework Symfony. A total of 69.9 percent of requirements were met. The agile work process proved to alleviate the implementation of functionality because of its flexibility, but work on functional tests and the database became more difficult.
Keywords: Data- och informationsvetenskap; Computer and Information Science